2014
DOI: 10.1016/j.jvs.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Aortic remodeling after thoracic endovascular aortic repair for intramural hematoma

Abstract: TEVAR is safe and effective in treating IMH and based on longitudinal computed tomography scan analysis, aortic remodeling is evidenced by normalization of all measured indices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…This mechanism may contribute to ideal remodeling of the affected aorta. In fact, Lavingia et al 37 demonstrated excellent results after 44 endovascular stent grafting for IMH B. At a mean radiological follow-up of 13 months, the average thickness of the IMH decreases to 4 mm (P ¼ 0.01, vs. preoperative of 12 mm).…”
Section: Discussionmentioning
confidence: 97%
“…This mechanism may contribute to ideal remodeling of the affected aorta. In fact, Lavingia et al 37 demonstrated excellent results after 44 endovascular stent grafting for IMH B. At a mean radiological follow-up of 13 months, the average thickness of the IMH decreases to 4 mm (P ¼ 0.01, vs. preoperative of 12 mm).…”
Section: Discussionmentioning
confidence: 97%
“…The proximal landing zone of the stent graft in the ruptured thoracic aortic aneurysm group was located near the aortic arch and was shorter and more curved than in the ruptured intramural hematoma group. The rupture sites in intramural hematomas are usually located in the straight descending thoracic aorta [22,23]. Therefore, a short, curved proximal landing zone might be related to endoleaks in ruptured thoracic aortic aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with IMH should receive initial medical therapy to control pain and blood pressure (level I, grade C) (36). TEVAR is safe and effective in treating IMH and also contributes to ideal remodeling of the affected aorta (60,61).…”
Section: Treatment: Medical Treatment or Surgical Intervention Open mentioning
confidence: 99%